Interocular Symmetry of Foveal Cone Topography in Congenital Achromatopsia. (2nd October 2020) - Litts, Katie M.; Georgiou, Michalis; Langlo, Christopher S.; Patterson, Emily J.; Mastey, Rebecca R.; Kalitzeos, Angelos; Linderman, Rachel E.; Lam, Byron L.; Fishman, Gerald A.; Pennesi, Mark E.; Kay, Christine N.; Hauswirth, William W.; et al.
ABSTRACT: Purpose : To determine the interocular symmetry of foveal cone topography in achromatopsia (ACHM) using non-confocal split-detection adaptive optics scanning light ophthalmoscopy (AOSLO). Methods : Split-detector AOSLO images of the foveal cone mosaic were acquired from both eyes of 26 subjects (mean age 24.3 years; range 8–44 years, 14 females) with genetically confirmed CNGA3 - or CNGB3 -associated ACHM. Cones were identified within a manually delineated rod-free zone. Peak cone density (PCD) was determined using an 80 × 80 μm sampling window within the rod-free zone. The mean and standard deviation (SD) of inter-cell distance (ICD) were calculated to derive the coefficient of variation (CV). Cone density difference maps were generated to compare cone topography between eyes. Results : PCD (mean ± SD) was 17, 530 ± 9, 614 cones/mm 2 and 17, 638 ± 9, 753 cones/mm 2 for right and left eyes, respectively ( p = .677, Wilcoxon test). The mean (± SD) for ICD was 9.05 ± 2.55 µm and 9.24 ± 2.55 µm for right and left eyes, respectively ( p = .410, paired t -test). The mean (± SD) for CV of ICD was 0.16 ± 0.03 µm and 0.16 ± 0.04 µm for right and left eyes, respectively ( p = .562, paired t -test). Cone density maps demonstrated that cone topography of the ACHM fovea is non-uniform with local variations in cone density between eyes. Conclusions : These results demonstrate the interocular symmetry of the foveal cone mosaic (both density and packing) in ACHM. As cone topography can differ between eyes of a subject, PCD does not completely describe the foveal cone mosaic in ACHM. Nonetheless, these findings are of value in longitudinal monitoring of patients during treatment trials and further suggest that both eyes of a given subject may have similar therapeutic potential and non-study eye can be used as a control.